The Influence of Dental Occlusion on Dynamic Balance and Muscular Tone - Julià-Sánchez, Sonia; Álvarez-Herms, Jesús; Cirer-Sastre, Rafel; Corbi, Francisco; Burtscher, Martin (Frontiers in Physiology, 2020)
Excellent postural control is essential to improve physical performance of athletes. Stability of the body during motor tasks depends on different physiological systems. The influence of dental occlusion on body balance has been widely investigated in the past few years. It has been suggested that this relationship is strengthened by disturbing environments for balance control (i.e. unstable platform, fatigue, development tasks...). Moreover, dental occlusion may influence the muscle tone of both masticatory and postural muscles, which are involved in the preservation of balance. Therefore, we attempted to determine whether (i) there are differences in dynamic balance assessed by the Modified Star Excursion Balance Test between opposed dental occlusion conditions (dental contact: Intercuspal position (ICP)/no dental contact: Cotton rolls mandibular position (CR)) and (ii) dental occlusion influences the biomechanical and viscoelastic properties of the masticatory and postural muscles assessed with MyotonPRO. Thirty physically active subjects were recruited for the study. The main findings were: (i) the SEBT Composite score was significantly higher for measurements made in CR (p < 0.001) and also in subjects showing an ideal occlusion (p=0.04), (ii) the biomechanic and viscoleastic properties of selected muscles showed different trend according to the presence of malocclusal traits. It is concluded that dental occlusion conditioned both dynamic stability and the biomechanic and viscoelastic properties of the analyzed muscles.